EKSPLORASI ILMIAH DAN PROSEDUR BERPIKIR ILMIAH DALAM MENINGKATKAN HIGHER-ORDER THINKING SKILLS PADA PENDIDIKAN DASAR DAN MENENGAH - Dewi Wulandari; Siminto; Yatin Mulyono (STKIP Subang, 2026)
This study aims to analyze the contribution of scientific exploration and scientific thinking procedures toward improving students’ Higher-Order Thinking Skills (HOTS) at the elementary and secondary education levels. The research method used was a literature study by analyzing various previous studies related to the development of higher-order thinking skills through scientific approaches and active learning models. The results showed that the low level of students’ HOTS was caused by the dominance of conventional learning and the use of teaching materials that did not sufficiently stimulate critical thinking skills. However, through the implementation of scientific exploration activities such as debates, discussions, discovery learning, and guided inquiry, students were able to develop their analyzing, evaluating, and creating skills more optimally. The findings also indicate that systematic scientific thinking procedures help students process information critically so that HOTS can develop effectively. The implication of this study emphasizes the importance of teachers designing contextual learning and using teaching materials that encourage students to think critically rather than merely focusing on memorization.